INFLUENCE STRATEGY LEARNING BASED PROBLEMS WITH THE CONVENTIONAL LEARNING TO STUDENT LEARNING OUTCOMES - Ratelit Tarigan (Jurnal Pendidikan Fisika, 2013)
This study aims to determine the differences in learning outcomes of students who use learning strategies based on problems with the conventional instructional strategies in the subject matter and measuring student learning activities when using learning strategies based on problems with conventional learning. The study was quasi-experimental. The population is all class X Semester Gasal SMA Swasta Martadinata consisting of 9 classes. Sampling was done by cluster random sampling by taking 2 classes of 9th grade classes were randomly ie X-7 as the experimental class and numbered 34, the class X-6 as a control class numbered 35 people. The results showed the average value of the experimental class pretest 32.20 with a standard deviation of 12.40 and a control class 31.40 with a standard deviation of 10.90. After completion of learning is given, the value of the average post-test on the experimental class of 76.50 with a standard deviation of 9.20 and a control class is 69.00 with a standard deviation of 9.10. T-test analysis results of the two parties obtained tcount = 3.42, while for ttable = 1.67 so that tcount > ttable. This means that Ha is accepted and Ho is rejected, or is there a significant difference between the learning outcomes of students who use learning strategies based on problems with student learning outcomes using conventional learning.